Cross mapping between clinical indicators for assistance in intensive care and nursing interventions - Maryanni Magalhães Camargo; Lorena Barros Furieri; Eliane de Fátima Almeida Lima; Amália de Fátima Lucena; Mirian Fioresi; Walckiria Garcia Romero (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: Identify the main clinical indicators for assistance in the Intensive Care Unit (ICU) and map them in the nursing interventions described by the Nursing Interventions Classification (NIC). Methods: Integrative literature review study, followed by cross-mapping between clinical indicators for assistance in the ICU care and NIC nursing interventions and activities. Results: 36 articles were identified, which resulted in 285 clinical indicators for ICU care, with mechanical ventilatory assistance, pain, sedation, psychomotor agitation, delirium, anxiety, altered heart rate, diet by naso tube / oroenteral and diarrhea the clinical indicators for assistance in the ICU the most prevalent. These were mapped in 12 Nursing Interventions Classification interventions and 130 nursing activities. Final considerations: It is concluded that the clinical indicators for ICU care associated with Nursing Interventions Classification are concrete data that assist intensive care nurses in their clinical practice.